(untitled) (Veterinary Science Development, 2015)
In recent years more attention has been given to herbal drugs in the treatment and prevention of drug toxicity because of the harmful effects of chemical drugs. In this study, directed for this purpose, research was conducted on the protective effect of hydro-ethanolic extract of saffron petals (SPE) against acetaminophen (APAP) induced acute nephrotoxicity. Twenty-four male Wistar rats were distributed into four groups of six each. Group I, as a control group, received normal saline (0.09%) orally (PO). Group II, as an intoxicated group was treated with APAP, PO (600 mg/kg). In the groups III and IV, SPE in a dose of 10 and 20 mg/kg along with APAP (600 mg/kg) was administered, respectively. At the end of the trial (8th day), blood was taken from the heart of rats for assessment of biochemical parameters and the right kidney was placed in 10% buffered formalin for histopathological evaluations. In the APAP treatment group, higher serum creatinine and uric acid were observed. SPE in a dose of 20 mg/kg significantly reduced serum creatinine and uric acid. In pathologic evaluation, a dose of 20 mg/kg of SPE prevented the kidney injuries induced by APAP. Tissues changes were in accordance with biochemical findings. It is likely that the SPE contributed to the prevention of acute nephrotoxicity induced by APAP.